Organizational effects during the covid-19 pandemic: The case of conamovidi and self-managed dining rooms - Atencio Becerra, William Junior (2021)
This article is based on information collected as part of a preliminary study on the situation of comedores autogestionarios (self-managed kitchens) in the context of the COVID-19 pandemic. The character of the study was exploratory and descriptive; with the method of grounded theory start with concepts of organization and biosafety The technique of in-depth interviews using telephone calls and virtual meetings used to apply the semi-structured questionnaire. The basic unit of analysis was the organization of the comedores autogestionarios belonging to CONAMOVIDI. The case study consists of five members, among leading members of the organization. Results: Three categories were obtained: Food management (main aim of the organization), biosecurity management (produced by the COVID-19 pandemic) and organizational dynamics (internal and external processes). These categories represent, in a first approximation, the situational reality of comedores autogestionarios or organizations with the same aim, in it during the obligatory social immobilization implemented by the Peruvian State.